2023
DOI: 10.1002/chem.202300641
|View full text |Cite
|
Sign up to set email alerts
|

Latent Pronucleophiles in Lewis Base Catalysis: Enantioselective Allylation of Silyl Enol Ethers with Allylic Fluorides

Abstract: Lewis base catalyzed allylations of C-centered nucleophiles have been largely limited to the niche substrates with acidic CÀ H substituted for CÀ F bonds at the stabilized carbanionic carbon. Herein we report that the concept of latent pronucleophiles serves to overcome these limitations and allow for a variety of common stabilized C-nucleophiles, when they are introduced as the corresponding silylated compounds, to undergo enantioselective allylations using allylic fluorides. The reactions of silyl enol ether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In accordance with previous literature reports, we observed that the MBH fluoride 1 undergoes nucleophilic substitution at the allylic carbon when treated with silyl enol ethers 2 and 3 in the presence of catalytic amounts of DABCO, and we obtained 4 and 5 in 10% and 85% yields, respectively. The low yield of 4 was attributed to the low stability of silyl enol ether 2 , which rapidly decomposed at room temperature.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous literature reports, we observed that the MBH fluoride 1 undergoes nucleophilic substitution at the allylic carbon when treated with silyl enol ethers 2 and 3 in the presence of catalytic amounts of DABCO, and we obtained 4 and 5 in 10% and 85% yields, respectively. The low yield of 4 was attributed to the low stability of silyl enol ether 2 , which rapidly decomposed at room temperature.…”
Section: Introductionsupporting
confidence: 92%
“…We have become increasingly interested in the development of synthetic methodologies that provide unique access to multifunctional compounds and exploit new reactivity patterns, in particular when these complement the outcome of existing reactions. To this end, we noticed that Shibata, Vilotijevic, and co-workers exploited silylated pronucleophiles that typically react at the allylic position in Morita–Baylis–Hillman (MBH) fluorides. By contrast, we envisioned that fluoride displacement might also be possible via attack at the vinylic carbon. Herein, we report that such a pathway by which the fluoride is replaced via formal S N 2′ reaction can indeed be realized through activation with inexpensive lithium iodide at room temperature (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the weak nucleophilicity of the nitrogen atom in indoles commonly resulted in the C2 or C3-positions alkylated by-products. In order to increase the N -centered nucleophilicity, an alternative method is the introduction of a protecting group at the N 1-position of indoles made it latent nucleophiles [ 24 , 25 , 26 , 27 ], which are themselves not nucleophilic but can produce a strong nucleophile in situ via deprotection. To the best of our knowledge, it was only in 2019 that the Vilotijevic group reported that N -silyl indoles were employed as latent N -centered nucleophiles in the substitution of allylic fluorides for N -allyl indoles [ 28 ].…”
Section: Introductionmentioning
confidence: 99%